Pan-Family Assays for Rapid Viral Screening: Reducing Delays in Public Health Responses During Pandemics. (20th July 2020) - Erlichster, Michael; Chana, Gursharan; Zantomio, Daniela; Goudey, Benjamin; Skafidas, Efstratios
Abstract: Background: Coronavirus disease 2019 has highlighted deficiencies in the testing capacity of many developed countries during the early stages of pandemics. Here we describe a strategy using pan-family viral assays to improve early accessibility of large-scale nucleic acid testing. Methods: Coronaviruses and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were used as a case study for assessing utility of pan-family viral assays during the early stages of a novel pandemic. Specificity of a pan-coronavirus (Pan-CoV) assay for a novel pathogen was assessed using the frequency of common human coronavirus (HCoV) species in key populations. A reported Pan-CoV assay was assessed to determine sensitivity to 60 reference coronaviruses, including SARS-CoV-2. The resilience of the primer target regions of this assay to mutation was assessed in 8893 high-quality SARS-CoV-2 genomes to predict ongoing utility during pandemic progression. Results: Because of common HCoV species, a Pan-CoV assay would return false positives for as few as 1% of asymptomatic adults, but up to 30% of immunocompromised patients with respiratory disease. One-half of reported Pan-CoV assays identify SARS-CoV-2 and with small adjustments can accommodate diverse variation observed in animal coronaviruses. The target region of 1 well-established Pan-CoV assay is highly resistant to mutation compared to species-specific SARS-CoV-2 reverse transcriptase-polymerase chain reaction assays. Conclusions: Despite cross-reactivity with common pathogens, pan-family assays may greatly assist management of emerging pandemics through prioritization of high-resolution testing or isolation measures. Targeting highly conserved genomic regions make pan-family assays robust and resilient to mutation. A strategic stockpile of pan-family assays may improve containment of novel diseases before the availability of species-specific assays. Abstract : SARS-CoV-2 has highlighted deficiencies in the testing capacity of many countries during the early stages of pandemics. Here, we describe a strategy using pan-family viral assays to improve early accessibility of large-scale nucleic acid testing.